Structural-Phase State and Mechanical Properties of the Surface Layer of the Copper Modified by Zirconium Ions; AIP Conference Proceedings; Vol. 2167 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2019 (AMHS'19) - Fedorishcheva M. V. Marina Vladimirovna; Kalashnikov M. P. Mark Petrovich; Bozhko I. A. Irina Aleksandrovna; Sergeev V. P. Viktor Petrovich (2019, 2019)
Title screen